(untitled) (Ágora de Heterodoxias, 2026)
In this issue, Ágora de Heterodoxias reaffirms its commitment to critical, plural, and interdisciplinary reflection on contemporary challenges that permeate the worlds of work, science, technology, management, and human and social development. Faithful to the spirit that inspires the journal’s name - the agora as a public space for debate, confrontation of ideas, and collective construction of meaning - the texts gathered here challenge hegemonic approaches, question naturalized assumptions, and propose alternative readings of complex phenomena in our time. From a theoretical standpoint, this volume is situated within a horizon that recognizes the inadequacy of linear and one‑dimensional explanations for understanding realities marked by technological acceleration, the precarization of work, the environmental crisis, and the intensification of demands imposed on individuals and organizations. In this context, perspectives that engage with complexity, critique power structures, acknowledge the historicity of institutions, and consider the cognitive, emotional, and social processes that guide human action gain central importance.